Double-Block for Cesarean Section and Hysterectomy in a Patient with Severe Placenta Accreta Spectrum: Are Neuraxial Blocks a Better Option Nowadays? A Case Report - Holanda, Plínio; Melo, Isadora (Brazilian Journal of Case Reports, 2025)
The Placenta Accreta Spectrum is an anomaly in the placenta that adheres to the uterus and fails to separate from it at delivery, which can lead to massive hemorrhage. For the anesthesiologist, the decision between general anesthesia (risks of pulmonary aspiration and difficult airway) or neuraxial block (worsening of hemorrhagic shock) is challenging. Vascular surgeons have helped reduce the bleeding for many years, and some techniques are more efficient. Is this the moment to prefer a neuraxial block? We expect to show that both methods are possible, but since the advent of vascular devices, neuraxial blocks are less harmful as these devices can reduce bleeding rates.